1991
DOI: 10.1523/jneurosci.11-04-01049.1991
|View full text |Cite
|
Sign up to set email alerts
|

The N-methyl-D-aspartate antagonist, MK-801, fails to protect against neuronal damage caused by transient, severe forebrain ischemia in adult rats

Abstract: The neuroprotective effects of dizocilipine maleate (MK-801), a noncompetitive antagonist of the N-methyl-D-aspartate (NMDA) receptor/channel, were tested in the 4-vessel occlusion rat model of forebrain ischemia. Adult Wistar rats, treated intraperitoneally with MK-801 or saline using several different treatment paradigms were subjected to 5 (n = 208) or 15 (n = 62) min of severe, transient forebrain ischemia. In saline-treated animals, 15 min of ischemia (n = 13) produced extensive and consistent loss of pyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(68 citation statements)
references
References 57 publications
5
62
1
Order By: Relevance
“…In the present study, we chose to administer MK801 systemically with a relatively higher dose of 7.5 mg/mg, at which all the animals in MK801-treated group survived well during the 4 h period of observation. Furthermore, considering the 1 h plasma half-life time of MK801 in rats, 45 we treated the animals with MK801 repetitively before and after SCI, bilateral CAO with hypotension 67 ± 69 or vertebral artery occlusion in rats 70,71 pretreatment: 0.1 ± 10 mg/kg, iv/ip 67,71 neuronal damage and microglial activation 72 reduced microglial activation and neuronal death of CA1 72 or did not prevent neuronal damage 67,71 67,71,72 posttreatment: 0.1 ± 5.0 mg/kg, ip/iv, immediately 20 h after reperfusion 67,71 neuronal damage and working memory 70 no neuroprotection 67,68,71 or decreased cell loss within 5 h injection after ischemia 69 and injected the drug slowly (16 min/infusion). MK801 delivered in this way has been shown to produce neuroprotection in experimental cerebral ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we chose to administer MK801 systemically with a relatively higher dose of 7.5 mg/mg, at which all the animals in MK801-treated group survived well during the 4 h period of observation. Furthermore, considering the 1 h plasma half-life time of MK801 in rats, 45 we treated the animals with MK801 repetitively before and after SCI, bilateral CAO with hypotension 67 ± 69 or vertebral artery occlusion in rats 70,71 pretreatment: 0.1 ± 10 mg/kg, iv/ip 67,71 neuronal damage and microglial activation 72 reduced microglial activation and neuronal death of CA1 72 or did not prevent neuronal damage 67,71 67,71,72 posttreatment: 0.1 ± 5.0 mg/kg, ip/iv, immediately 20 h after reperfusion 67,71 neuronal damage and working memory 70 no neuroprotection 67,68,71 or decreased cell loss within 5 h injection after ischemia 69 and injected the drug slowly (16 min/infusion). MK801 delivered in this way has been shown to produce neuroprotection in experimental cerebral ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…The effect was statistically significant (p < 0.05). However, vitamin E and TF 100 mg/kg showed an increase in neuronal density in the CA1 field of the tGCI rat brain but it was not found to be statistically significant (Buchan et al, 1991).…”
Section: Histopathological Examinationmentioning
confidence: 71%
“…Rectal temperature was maintained at 37 ± 0.5°C during the surgical procedures to avoid hypothermia. Sham operated animals were treated similarly to the ischemic group but the common carotid and vertebral arteries were not occluded (Buchan et al, 1991).…”
Section: Hptlc Analysis Of Terpenoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…nist of NMDA-induced excitotoxicity Rod and Auer, 1989), subsequent work disclosed prolonged hypothermia in MK-801-treated isch emic animals, which was required for its therapeu tic effect (Buchan and Pulsinelli, 1990;Corbett et al, 1990). In an extensive study, a protective effect of MK-801 could not be demonstrated in tempera ture-regulated normothermic rats exposed to 5 or 15 min of four-vessel occlusion despite the use of a wide range of MK-801 dosing regimens (Buchan et al, 1991). We and others have shown that mild de grees of brain hypothermia, by itself, are markedly protective in ischemia (Busto et al, 1987(Busto et al, , 1989aMinamisawa et al, 1990a,b;Chopp et al, 1991;Ginsberg et al, 1992) and that this is related, at least in part, to the inhibition of glutamate release (Busto et al, 1990), as well as protection against blood brain barrier dysfunction (Dietrich et al, 1990 Intriguingly, it has been in animal models of focal cerebral ischemia that the most convincing evi dence of MK-801 's cerebroprotective efficacy has emerged (Kochhar et al, 1988;Ozyurt et al, 1988;Park et al, 1988a,b;Dirnagl et al, 1990;Bielenberg and Beck, 199 1;Gill et al, 1991;Buchan et al, 1992;Roussel et aI., 1992).…”
Section: Resultsmentioning
confidence: 99%